Parental Impact on Succession in Russian Family Enterprises - Shiriev, Ramil (2024)
Succession in the family business represents a critical transition period that has a significant impact on the preservation of the identity and structure of the business. This process includes the transfer of managerial control, the preservation of family values and cultural heritage, as well as the determination of the strategic orientation of the enterprise. The psychological and emotional aspects of this process may result in stress for business successors. In this regard, the parents play a defining role, where their participation and influence on the future successor and their decisions are of crucial importance. In this respect, the purpose of this study is to analyze the influence of parents on the succession process in Russian family businesses.